Session-Specific Effects on Suicidality in Group Therapy: No Evidence for Contagion. Issue 2 (3rd April 2023) - Miegel, Franziska; Peth, Judith; Rubel, Julian; Runde, Anne; Arlt, Sönke; Gallinat, Jürgen; Jelinek, Lena
Abstract: Objective: Explicitly addressing suicidality in group therapy is often avoided due to the fear of contagion effects. However, there is some evidence that this fear is not valid. Therefore, the present study aims at contributing to this question by investigating the session-specific effects of two modules on suicidality that are part of the Metacognitive Training for Depression (D-MCT/S). Methods: Forty-four patients with depression participated in the two modules on suicidality of the D-MCT/S. Before and after each group session, patients filled out a questionnaire asking for symptoms of suicidality, associated cognitions (e.g., hopelessness), and associated emotions (e.g., anger). Data were analyzed by linear mixed-effect models. Results: Approximately 84% of the patients had experienced lifetime suicidal ideation. No within- or between-session effects were found for the modules on suicidality. Sample size was large enough to find small to medium effects (within-session analyses) and medium to large effects (between-session analyses). Conclusion: The modules on suicidality did not specifically change suicidal symptoms or associated cognitions and emotions immediately or by the next session. Most importantly, our results disconfirm evidence on deterioration when suicidality is addressed in a highly structured group setting. Whether the current findings also apply to other forms of group therapies needs to be investigated in future studies. HIGHLIGHTS: Session-specific investigations allow a thoroughly examination of an intervention Metacognitive Training for Depression showed no contagion effect on suicidality